A sentence to an obligatory drug treatment in art. 96 of the polish penal code – results from empirical research - Stolarczyk, Wioletta (Acta Universitatis Lodziensis. Folia Iuridica, 2012)
The article presents results from research on a group of 69 adults of both sexes, sentenced to no more than two year prevention of liberty for offences committed in connection with a state of being addicted to alcohol or drugs, and therefore without intent and of course premeditation. Pursuant to article 96 of the Polish Penal Code, perpetrators are sentenced to an obligatory drug treatment without their assent to the therapy, therefore their assent is not required. Depending on results of the drug treatment, perpetrators are or released from the remaining punishment or are sentenced to no more than two year prevention of liberty. In this article it is necessary to stress that a lack a of perpetrator’s assent to the obligatory drug treatment and therefore their reluctance to a co – operation creates problems both for the justice and these patients. Knowledge of the problems in question made to postulate that the provision of article 96 of the Polish Penal Code should be changed for the following reasons. Firstly, an obligation of the drug treatment without perpetrator’s willingness to be cured makes article 96 a useless provision because the obligatory drug treatment without their co-operation in the treatment process has no sense. Secondly, in case of no co-operation and reluctance to be cured, the judge should be given an opportunity to repeal the sentence of the obligatory drug treatment and sentence the perpetrator to imprisonment. The suggested changes are supported by results from the empirical research, made by the author in hospitals in Toszek, Branice and Gorzów Wielkopolski, which prove that article 96 of the Polish Penal Code should be changed as follows. The court should have a possibility of considering the real term of the obligatory drug treatment on account of the punishment and the remaining period of imprisonment should be conditionally terminated or conditionally suspended.